"I tremble with my whole heart": Cicero on the anxieties of eloquence. (October 2021) - Goodman, Rob
Cicero's rhetorical theory offers an important critique of efforts to systematize persuasion. His resistance to this systematization is grounded in his reconception of the orator's virtus, which, amidst the crisis of the late Roman Republic, he reimagines as a capacity to endure risk in confrontation with an unruly public. In order to stress this risk, he must at the same time valorize the uncertainties of language: the absence of predictable, manipulable links between speech and audience response. Because this model of eloquence implies that the rhetorical audience cannot and should not be systematized, it places surprising pressures on Cicero's elitism. This article examines Cicero's antipathy toward the routinization of rhetoric, contrasts it with the more rationalized model of speech in De analogia, Julius Caesar's fragmentary work on style, and considers how Cicero's stress on the autonomy of the rhetorical audience can be recovered as a resource for democratic theory.